Molecular rules for selectivity in lipase-catalysed acylation of lysine. (November 2018) - Dettori, L.; Jelsch, C.; Guiavarc'h, Y.; Delaunay, S.; Framboisier, X.; Chevalot, I.; Humeau, C.
Graphical abstract: Highlights: The N -acylation of lysine catalysed by Candida antarctica lipase B was studied. A methodology for explaining the selectivity of the reaction was developed. Acylation took place selectively on the lysine epsilon amino group. Molecular rules for selectivity were proposed based on interaction mapping analysis. Abstract: The selectivity ofl -lysine acylation by lauric acid catalysed by Candida antarctica lipase B (CALB) was investigated combining experimental and theoretical methodologies. Experiments showed the near-exclusive acylation of lysine ε-amino group; only traces of product resulting from the acylation of lysine α-amino group were observed fleetingly. Molecular modelling simulations were performed aiming to understand the molecular rules for selectivity. Flexible docking simulations combined with structural investigations into lysine/CALB binding modes also suggested the preferential acylation of the lysine ε-amino group without, however, excluding the acylation of the lysine α-amino group. Electrostatic interaction energy between lysine and the residues covering the catalytic cavity was calculated in order to understand the discrimination between the two lysine amino groups. Key interactions with the polar region covering the catalytic triad were identified and a plausible explanation for selectivity was proposed.